Tratamento do adulto com leucemia mielóide aguda em países em desenvolvimento: experiência do Hospital das Clínicas - UFMG - Evandro Maranhao Fagundes (2004)
We have described that socioeconomic status (SES) is associated with outcomes of ALL childhood and may he associated with AML outcomes as well. Complete remission (CR), overall survival (OS) and leukemia free survival (LFS) for adult AML treated in developing counries seem to be inferior to those reported in Europe and North American trials. We hare used the human development index (HDI) of the United Nations as a SES factor and associated it with death at induction, CR, use of high dose Ara-C (Hidac), OS and LFS of adult patients with "de novo" AML. Among 124 consecutive patients retrospectively analyzed, 46 (37 %) died during induction, 66 reached CR (53%) and 46 (37%) received Hidac consolidation. ln univariate and multivariate analyzes, the HDI lower than 0,660 was associated with lower chance to receive Hidac (p=0,001) and a trend for higher induction mortality (p=0,062).The OS and LFS at 5 years were 17%±3% and 26%±6% respectively for all patients and 36%±7% and 30%±7% respectively for those receiving Hidac. ln univariate analysis, the HDI was associated with OS (p=0.003) and in multivariate analysis vvith LFS (p=0,000). However it was not associated with survival for patients receiving Hidac (p=0,133). The survival for patients who received Hidac consolidation is similar to those reported in developed countries. However, the small number of patients receiving Hidac precluded better results. Poor SES. measured by HDI, may be a factor in patient selection for intensive treatment and consequently may be associated with survival.